Factors Affecting Formation of R&D Alliance : Case of MSC Companies - Chen, Nick Kid Khian (2005)
Confronted with the opening of world markets and intensified competition, companies at the Multimedia Super Corridor are searching for innovation through R&D. In their quest for efficient operation, firms increasingly revert to seeking new technologies via interfirm agreements, not only with suppliers and customers but also with competitors. The advantages of R&D alliance will be explored in this paper. The survey conducted using questionnaires sent by mail focused on three big areas, the motivation factors, risk factors and success & failure factors of R&D alliance. Our study on the R&D alliance shows that whilst firms have some common factors in forming an R&D alliance; technical compatibility, gain market power, market access the local and foreign firms have some dissimilarities in their motivations towards forming of R&D alliance. It is apparent that local firms seek strategic advantages of long term profitability, market access and improving competitive advantage. Foreign firms differ in terms of the importance of some motivational factors including technical compatibility, pooling of resources and minimizing regulatory cost. The survey also showed that risks faced by companies remain a concern among firms in R&D alliance. One of the major concerns is differing aims among alliance partners and leakage of information to the alliance partner. Attributes of partners are also important to the success or failure of an alliance. The four most important attribute of a partner include: top management commitment, favorable deal terms and frequent communication between partners. Until now, there has been no comprehensive study on the factors contributing to successful alliance formation from the point of view of the ICT industry in Malaysia. This survey analysis is devised to fill this gap.